Language and cognitive function in children: a narrative review of neural, behavioral, and developmental evidence - Pu, Ling; Kiselev, Sergey; Xiao, Ningkun (Frontiers in Psychology, 2025)
Language is not merely a conduit for thought-it plays an active, constitutive role in shaping cognitive development. This narrative review synthesizes interdisciplinary findings across bilingualism, theory of mind, developmental disorders (DLD and ASD), and cross-cultural studies to propose a dynamic, context-sensitive model of the language-cognition relationship. We argue that language functions not only as a cognitive tool but as a cognitive architect, influencing the structure and function of neural networks supporting executive function and social cognition. Evidence from behavioral and neuroimaging studies reveals bidirectional and developmentally contingent interactions between language and cognition, moderated by linguistic structure, developmental timing, and sociocultural context. By examining both typical and atypical populations, we challenge modular and unidirectional models, advocating instead for integrative frameworks that capture the diversity and plasticity of human cognition. We conclude with a roadmap for future research, emphasizing longitudinal, cross-linguistic, and translational approaches. This work calls for a rethinking of language's role-not as a passive reflection of mind, but as its formative force.